Gray Matter Loss and Related Functional Connectivity Alterations in A Chinese Family With Benign Adult Familial Myoclonic Epilepsy. Issue 42 (October 2015) - Zeng, Ling-Li; Long, Lili; Shen, Hui; Fang, Peng; Song, Yanmin; Zhang, Linlin; Xu, Lin; Gong, Jian; Zhang, Yunci; Zhang, Yong; Xiao, Bo; Hu, Dewen
Abstract : Abstract: Benign adult familial myoclonic epilepsy (BAFME) is a non-progressive monogenic epilepsy syndrome. So far, the structural and functional brain reorganizations in BAFME remain uncharacterized. This study aims to investigate gray matter atrophy and related functional connectivity alterations in patients with BAFME using magnetic resonance imaging (MRI). Eleven BAFME patients from a Chinese pedigree and 15 matched healthy controls were enrolled in the study. Optimized voxel-based morphometric and resting-state functional MRI approaches were performed to measure gray matter atrophy and related functional connectivity, respectively. The Trail-Making Test-part A and part B, Digit Symbol Test (DST), and Verbal Fluency Test (VFT) were carried out to evaluate attention and executive functions. The BAFME patients exhibited significant gray matter loss in the right hippocampus, right temporal pole, left orbitofrontal cortex, and left dorsolateral prefrontal cortex. With these regions selected as seeds, the voxel-wise functional connectivity analysis revealed that the right hippocampus showed significantly enhanced connectivity with the right inferior parietal lobule, bilateral middle cingulate cortex, left precuneus, and left precentral gyrus. Moreover, the BAFME patients showed significant lower scores in DST and VFT tests compared with the healthy controls. The gray matter densities of the right hippocampus, right temporal pole, and left orbitofrontal cortex were significantly positively correlated with the DST scores. In addition, the gray matter density of the right temporal pole was significantly positively correlated with the VFT scores, and the gray matter density of the right hippocampus was significantly negatively correlated with the duration of illness in the patients. The current study demonstrates gray matter loss and related functional connectivity alterations in the BAFME patients, perhaps underlying deficits in attention and executive functions in the BAFME.